GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 03 Jun 2020, 22:04 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  # If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =

Author Message
TAGS:

### Hide Tags

GMAT Club team member V
Status: GMAT Club Team Member
Affiliations: GMAT Club
Joined: 02 Nov 2016
Posts: 5957
GPA: 3.62
If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

1
1 00:00

Difficulty:   5% (low)

Question Stats: 65% (00:42) correct 35% (01:29) wrong based on 46 sessions

### HideShow timer Statistics

If $$x = -1$$ then $$x^4 - x^3 + x^2 - x^1 + x^0 =$$

A. -3

B. -2

C. 3

D. 4

E. 5

_________________
Senior Manager  G
Joined: 28 Jun 2019
Posts: 469
Re: If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

3
If $$x = -1$$ then $$x^4 - x^3 - x^2 - x^1 - x^0 =$$

A. -3

B. -2

C. 3

D. 4

E. 5

Am I wrong?
Each number to the power of 0 equals 1.
So -1 ^0= 1
So , -1^4 - (-1^3)-(-1^2)-(-1)-1=1
But there is not among options.

Posted from my mobile device
_________________
Always waiting
Intern  B
Joined: 13 Mar 2018
Posts: 6
Re: If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

My answer is coming as 1 but the in option not given.
My approach-

x = -1
then x^4 - x^3 - x^2 - x^1 - x^0

= (-1)^4-(-1)^3-(-1)^2-(-1)^1-(-1)^0
=1+1-1+1-1
=1
Intern  B
Joined: 12 Aug 2019
Posts: 1
Re: If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

1
As the value of X=-1, so even power will be positive so the solution is:
(-1)^4-(-1)^3-(-1)^2-(-1)^1-(-1)^0
=1-(-1)-(1)-(-1)-(-1)
=1+1-1+1+1
=3
VP  V
Joined: 27 May 2012
Posts: 1042
If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

1
meht wrote:
As the value of X=-1, so even power will be positive so the solution is:
(-1)^4-(-1)^3-(-1)^2-(-1)^1-(-1)^0
=1-(-1)-(1)-(-1)-(-1)
=1+1-1+1+1
=3

meht $$(-1)^0=1$$ and NOT -1 so you should get 1+1-1+1-1=1
_________________
- Stne

Originally posted by stne on 16 Aug 2019, 10:37.
Last edited by stne on 16 Aug 2019, 10:55, edited 1 time in total.
GMAT Club team member V
Status: GMAT Club Team Member
Affiliations: GMAT Club
Joined: 02 Nov 2016
Posts: 5957
GPA: 3.62
Re: If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

Thank you! edited, kindly refresh the page.

stne wrote:
meht wrote:
As the value of X=-1, so even power will be positive so the solution is:
(-1)^4-(-1)^3-(-1)^2-(-1)^1-(-1)^0
=1-(-1)-(1)-(-1)-(-1)
=1+1-1+1+1
=3

meht $$(-1)^0=1$$ and NOT -1 so you should get 1+1+-1+1-1=1

_________________
Director  V
Joined: 30 Sep 2017
Posts: 928
GMAT 1: 720 Q49 V40 GPA: 3.8
If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

1
$$x^4 - x^3 - x^2 - x^1 + x^0$$
$$= (-1)^4-(-1)^3-(-1)^2-(-1)^1+(-1)^0$$
$$= 1 + 1 + 1 + 1 + 1 = 5$$

Posted from my mobile device

Originally posted by chondro48 on 16 Aug 2019, 16:40.
Last edited by chondro48 on 10 Sep 2019, 04:29, edited 2 times in total.
CEO  V
Joined: 03 Jun 2019
Posts: 2931
Location: India
GMAT 1: 690 Q50 V34 WE: Engineering (Transportation)
Re: If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  [#permalink]

### Show Tags

If $$x = -1$$ then $$x^4 - x^3 + x^2 - x^1 + x^0 =$$

A. -3

B. -2

C. 3

D. 4

E. 5

1+1+1+1+1=5

IMO E

Posted from my mobile device
_________________
Kinshook Chaturvedi
Email: kinshook.chaturvedi@gmail.com Re: If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =   [#permalink] 16 Aug 2019, 17:56

# If x = -1 then x^4 - x^3 - x^2 - x^1 - x^0 =  